THE HISTORICAL ROOTS OF A. E. NORDENSKIÖLD’S (1832–1901) CONSERVATIONAL PHILOSOPHY - Niemi SA (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
One of the founding texts within the history of Nordic conservation is 'Forslag till inrattandet af Riksparker i de nordiska landerna' (A Proposal for Establishing Nation's Parks in the Nordic Countries), written by the Finnish-Swedish scientist and explorer Adolf Erik Nordenskiold (1832-1901) in 1880. It is comparable to influential texts of US environmental history, such as George Catlin's Illustrations of the Manners, Customs, and Condition of the North American Indians (1845-1848) and George Perkins Marsh's Man and Nature (1864). The ideas developed in the essay are expressions of an environmentally literate person. Nordenskiold perceived destructive developments taking place in the environment and set down proposals to prevent or remedy this undesirable situation. This article will discuss the historical roots of Nordenskiold's conservational philosophy, such as the modernization process, patriotic ideas from the Romantic era, and, above all, the influence of US thinkers, most notably George Catlin, who proposed the opening of 'nation's Parks [ horizontal ellipsis ] on the great plains of the West'. The influence of Nordenskiold on the subsequent conservation movement in Finland and in Sweden will be examined in detail. The first national parks in Europe were established in Sweden in 1909.